2017
DOI: 10.1002/marc.201700315
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Unimolecular Micelles with Incorporated Hyperbranched Boltorn H30 Polyester modified with Hyperbranched Helical Poly(phenyl isocyanide) Chains and their Enantioselective Crystallization Performance

Abstract: Here, the fabrication of unimolecular micelles functionalized with helical polymeric chains as a chiral nucleating agent in enantioselective crystallization is reported. Starting from a fractionated hyperbranched polyester (Boltorn H30), the ring-opening polymerization of l-lactic acid (LLA) and subsequent terminal-group modification affords the alkyne-Pd(II)-anchored hyperbranched macroinitiator (H30-PLLA-Pd). By taking advantage of a Pd(II)-catalyzed living polymerization of chiral pendant modified l- or d-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…225 This approach enables coupling of the polymer scaffold to a variety of substituents such as dyes or other polymers to generate (block) copolymers. 222,226,227 While the introduction of a handle via initiator modification is an elegant functionalization strategy, its applications are restricted, analogous to electrochemical coupling and ROP initiator modification mentioned earlier.…”
Section: Poly(isocyanide)smentioning
confidence: 99%
“…225 This approach enables coupling of the polymer scaffold to a variety of substituents such as dyes or other polymers to generate (block) copolymers. 222,226,227 While the introduction of a handle via initiator modification is an elegant functionalization strategy, its applications are restricted, analogous to electrochemical coupling and ROP initiator modification mentioned earlier.…”
Section: Poly(isocyanide)smentioning
confidence: 99%
“…Hyperbranched polymers are drawing more and more attention especially in the fields of self-assembly owing to their specific size, shape and properties. Many impressive supermolecucular aggregates at all scales and dimensions have been obtained [14][15][16], such as unimolecular micelles, polymer vesicles, composite vesicles and macroscopic tubes. Further research about amphiphilic hyperbranched polymers have been demonstrated unique advantages in supramolecular self-assembly behaviors, including special properties, unique self-assembly mechanisms and functionalization processes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group reported a family of alkyne‐Pd(II) complexes which can initiate the living polymerization of isocyanide monomers and lead to the formation of stereoregular helical polyisocyanides with controlled molar masses ( M n s) and narrow molar mass distributions ( M w / M n s). Moreover, these Pd(II) complexes are efficient catalyst with tolerance to most organic solvents and easy to be synthesized …”
Section: Introductionmentioning
confidence: 99%